PEDAGOGICAL MODEL FOR TEACHING GENERAL MILITARY DISCIPLINES IN MILITARY HIGHER EDUCATION INSTITUTIONS UNDER A COMPUTER-ORIENTED LEARNING ENVIRONMENT - Rybchuk, Oleh; Yaroshov, Mykola (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Amidst the Russo-Ukrainian war and the increasing significance of information technologies in military education, the need for optimizing pedagogical methods becomes apparent. This article explores innovative approaches to education in higher military institutions, emphasizing the importance of integrating a computer-oriented learning environment into the teaching process. Such integration not only enhances the skillset of the officer corps but also ensures the effectiveness of training that meets contemporary demands. Furthermore, the article proposes the justification and development of a pedagogical model for teaching general military disciplines, unveiling its structure, core components, and methods for implementation in the educational process for reserve officers. It also identifies the psycho-pedagogical conditions that facilitate the successful introduction of educational innovations based on a computer-oriented learning environment, opening new perspectives for military education.M e t h o d s . The study is based on the theoretical examination of scholarly works in the field of educational technologies and their application to military training, as well as data analysis from the past and forecasting the future. Efforts are also concentrated on developing and substantiating a pedagogical model that integrates these technologies into the learning process.R e s u l t s . The developed model includes electronic educational resources, multimedia materials, and specialized software that facilitates both collective and individual learning processes. It supports a practical interactive experience, extremely crucial for advanced military education.C o n c l u s i o n s . The implementation of a computer-oriented learning environment has the potential to significantly enhance educational achievements, providing a more engaging, interactive, and versatile learning experience. This environment paves the way for the development of essential military competencies and the improvement of the overall educational system in military educational institutions.
Keywords: general military disciplines, computer-oriented learning environment, pedagogical model, interactive teaching tools, information and communication technologies, teaching methodology for general military disciplines